KADAR KOLESTEROL HDL TERUKUR MENGGUNAKAN REAGEN CHOLESTEST N HDL DAN HDL-C PLUS GENERASI KETIGA - Ichwan Meinardi; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
The using of the open reagent system tools gives the possibility to choose the best quality of reagents including the reagent for HDLcholesterol concentration test. Hitachi 902 (Roche) as an open reagent system tool may used Cholestest N HDL (Daichi) as the firstHDL reagent and HDL-C plus 3rd generation reagent (Roche). The aim of this study was to know the correlation of HDL cholesterolconcentrations using Cholestest N HDL and HDL-C plus 3rd generation reagents measured by Hitachi 902. A cross sectional study wasdone from April to June 2008 at Ratulangi Medical Centre Laboratory, Makassar. The HDL cholesterol concentration was measured byHitachi 902 using Cholestest N HDL and HDL-C plus 3rd generation reagents. Sample was analyzed with SPSS 14 for Windows Programusing T test and Pearson Correlation. Among 80 samples we found the mean HDL concentration using Daichi reagent was 46.19 mg/dlranging from 34.99 mg/dl to 57.39 mg/dl and the mean using Roche 3rd reagent was 48.35 mg/dl ranging from 35.18 mg/dl to 61.52mg/dl, with p = 0.098 and Pearson Correlation was r = 0.967 with p = 0.000.There was no difference between HDL concentrationdetected by Cholestest N HDL and HDL-C plus 3rd generation reagents.